(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the supportive effect of cold plasma in wound care after abdominal surgery in cancer patients at Hợp Lực General Hospital. Materials and methods: Controlled intervention study on patients with abdominal wall incisions at the Oncology Department of Hop Luc General Hospital from January 2023 to December 2024. Results: The sensation of tightness and suture knots appeared in 8.9% of the plasma-treated group, which was lower than the 26.7% in the non-plasma group, with a statistically significant difference (p=0.027). On the 7th day after surgery, the plasma-treated group no longer felt the tension of the sutured tissue, while the group without plasma treatment still had 11.1%. The difference is statistically significant with p=0.021. The difference in early wound healing rates between the two groups was statistically significant (p<0.05). The group using cold plasma had lower pain levels on the 3rd, 5th and 7th postoperative days compared to the group not using plasma. The difference in pain reduction was statistically significant with p<0.05. The cold plasma procedure generally took 1-3 minutes. Most abdominal wounds were treated with cold plasma less than 10 times. The hospitalization time for the plasma-treated group (6.1 ± 1.1 days) was shorter than for the non-plasma group (7.1 ± 1.6 days), and this difference was statistically significant (p<0.05). 93.3% of the study subjects felt comfortable and did not experience risk factors such as electric shock, heat, or Argon gas poisoning. Only 6.7% of subjects reported itching (2.2%) and burning (4.5%) during plasma treatment. Conclusion: The use of cold plasma in abdominal wound care accelerates wound healing, reduces postoperative pain, lowers the risk of infection, and improves treatment efficacy. It makes wound care easier and allows for earlier discharge of patients.